2009
DOI: 10.1111/j.1440-1827.2009.02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Fumagillin inhibits colorectal cancer growth and metastasis in mice: In vivo and in vitro study of anti‐angiogenesis

Abstract: Fumagillin is an inhibitor of type 2 methionine aminopeptidase that can block blood vessel formation, but its molecular mechanism and therapeutic value in colon cancer still remain to be elucidated. In this study, male severe combined immunodeficiency (SCID) mice were injected with colon cancer cells in the subcutis and then treated with Fumagillin and Cyclo (Arg-Gly-Asp-D-Phe-Val), an integrin alphavbeta(3) antagonist. The tumor weight, microvessel density (MVD), and number of pulmonary metastatic foci were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The in vitro experiments, aside from SU5416, confi rmed the inhibitory action of Fumagillin, Artesunate, and 3,5,4´-Trimethoxystilbene on endothelial cells. A similar dose-dependent negative effect on the proliferation had been described recently in different types of endothelial cells (Wang et al, 2000;Chen et al, 2004;Dell`Eva et al, 2004;Hou et al, 2009;Alex et al, 2010). The POB-like cells were less affected by adding either antiangiogenic substances.…”
Section: Discussionsupporting
confidence: 79%
“…The in vitro experiments, aside from SU5416, confi rmed the inhibitory action of Fumagillin, Artesunate, and 3,5,4´-Trimethoxystilbene on endothelial cells. A similar dose-dependent negative effect on the proliferation had been described recently in different types of endothelial cells (Wang et al, 2000;Chen et al, 2004;Dell`Eva et al, 2004;Hou et al, 2009;Alex et al, 2010). The POB-like cells were less affected by adding either antiangiogenic substances.…”
Section: Discussionsupporting
confidence: 79%
“…It has been observed that in murine models of colorectal cancer, fumagillin and its derivative fr-11887 can inhibit colorectal growth and prevent metastasis [156,157]. On the other hand, it has also been demonstrated that the combination of fumagillin derivatives with antitumor molecules like 5-fluorouracil can inhibit the growth of colon adenocarcinoma tumor cell lines [158] or prolong its tumor growth inhibitory effect after the termination of treatment in an experimental murine model [159].…”
Section: Angiogenesis and Antitumor Activitiesmentioning
confidence: 99%
“…Furthermore, fumagillin arrests endothelial cells in G1 phase of cell cycle along with suppression of cyclin E mRNA expression and protein level resulting in the inhibition of endothelial cell proliferation and motility. Microarray analysis of fumagillin-treated HUVEC shows an upregulation of 71 genes and downregulation of 143 genes that are mostly involved in cell proliferation, migration, adhesion, differentiation, and gene transcription [46]. Low dose of fumagillin treatment to SCID mice bearing colon cancer cells in the subcutis when harvested after 4 weeks of treatment had small tumor mass, fewer pulmonary metastases, and lower microvessel density relative to control group [46].…”
Section: Fumagillinmentioning
confidence: 99%
“…Microarray analysis of fumagillin-treated HUVEC shows an upregulation of 71 genes and downregulation of 143 genes that are mostly involved in cell proliferation, migration, adhesion, differentiation, and gene transcription [46]. Low dose of fumagillin treatment to SCID mice bearing colon cancer cells in the subcutis when harvested after 4 weeks of treatment had small tumor mass, fewer pulmonary metastases, and lower microvessel density relative to control group [46]. Suppression of hepatoma growth and metastasis by fumagillin has also been reported [47].…”
Section: Fumagillinmentioning
confidence: 99%